2004
DOI: 10.1073/pnas.0308489101
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori interacts with the human single-domain trefoil protein TFF1

Abstract: Why Helicobacter pylori colonizes only gastric tissue is unknown. It is found on gastric mucus-secreting cells and in the overlying gastric mucus but not deep in gastric glands. This localization mirrors the expression of trefoil factor 1, TFF1. We hypothesized that H. pylori interacting with TFF1 could explain the tropism of this bacteria for gastric tissue. Recombinant human TFF1 expressed in Escherichia coli was purified by affinity chromatography, ionexchange chromatography, and gel filtration. Binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…Moreover, expression of the TFFs is increased during infection with H. pylori, which seems contradictory to the role of TFF1 in protecting and restituting the mucosa [228,229]. In addition, GKN2 is downregulated during infection with H. pylori [227], which may lead to even more TFF1 ready for interaction with the bacteria.…”
Section: Tff Binding Proteins or Receptorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, expression of the TFFs is increased during infection with H. pylori, which seems contradictory to the role of TFF1 in protecting and restituting the mucosa [228,229]. In addition, GKN2 is downregulated during infection with H. pylori [227], which may lead to even more TFF1 ready for interaction with the bacteria.…”
Section: Tff Binding Proteins or Receptorsmentioning
confidence: 91%
“…Interestingly, another study showed that Helicobacter pylori bound specifically and with high avidity to dimeric TFF1. This binding was necessary for binding of the bacteria to MUC5AC and thus for their selective colonization of the gastric mucosal surface [227]. Moreover, expression of the TFFs is increased during infection with H. pylori, which seems contradictory to the role of TFF1 in protecting and restituting the mucosa [228,229].…”
Section: Tff Binding Proteins or Receptorsmentioning
confidence: 98%
“…Another potential inhibitor has been investigated by Bai et al 30 An analogue of BabA, known as recombinant BabA (rBabA), was found to partially inhibit binding of H. pylori to gastric epithelial cells and significantly inhibit adhesion to the gastric cancer cell line MGC-803. If indeed TFF1 is a receptor for H. pylori in the human stomach, as suggested by Clyne et al 22 , then their studies have also demonstrated a potential anti-adhesion therapy. They found that adhesion of H. pylori to TFF1-dimer coated beads was inhibited by either pre-incubating the bacteria with soluble recombinant TFF1 or by pre-incubating the beads with anti-TFF1 monoclonal antibody.…”
Section: Adhesion At the Epithelial Surface And Inhibitor Developmentmentioning
confidence: 97%
“…In the gastrointestinal epithelium, TFF proteins are expressed in a site-specific manner, TFF1 being primarily located within the foveolar pit cells of the gastric body and superficial regions of the antral glands 21 . Studies by Clyne et al 22 have shown that H. pylori is able to bind to TFF1, suggesting that alongside Le b, TFF1 may also be a receptor for H. pylori in vivo and may provide another reason for its tropism for gastric tissue.…”
Section: Adhesion At the Epithelial Surface And Inhibitor Developmentmentioning
confidence: 99%
“…More recently, it has also been shown that TFF2 messenger RNA (mRNA) levels increase within minutes following gastric ulceration in rats [74], and TFF2-defi cient mice present a larger number of non steroidal anti-infl ammatory drug (NSAID)-induced ulcers when compared with wild-type animals [66]. Another interesting possibility results from the demonstration that TFF1 overexpression can confer on Helicobacter pylori an enhanced ability to colonize the gastric mucosa [75]. H. pylori infection fi rst induces chronic superfi cial (non-atrophic) gastritis, which can progress through chronic atrophic gastritis, intestinal metaplasia and dysplasia toward gastric cancer [76,77].…”
Section: Functional Role Of Tffs In Cancermentioning
confidence: 99%